Three-dimensional morphometric analysis of mandibular foramina: a cone beam computed tomography study comparing mahajir and pukhtoon ethnics in Pakistan - Alam, Beenish Fatima (2024)
A thorough understanding of the anthropometric landmarks on the mandible and their clinical application is necessary, before performing any surgical procedure to reduce the risk of inferior alveolar nerve injury. Cone bean computed tomography (CBCT) is a widely recognised diagnostic tool that generates high-quality, accurate images and assists in identifying the precise location of anatomical components. It has been utilised as instruments for facilitating preoperative planning of surgical procedures. This study aimed to identify the foramen located on the surface of mandible, and to determine their number, shape, classification, dimensions, position, and their distance to various anatomical landmarks. Another objective is to determine the association of mandibular foramen location with mandibular body and ramus height and length between sexes, between right and left sides, and between Mahajir and Pukhtoon ethnic groups of Pakistan. Four hundred CBCT from Mahajir and Pukhtoon Pakistani populations were collected from Khans Dental Institute, Karachi from 2016 to 2021. CBCT imaging was carried out using the New Tom VGi machine (NewTom Co., Ltd., Shawnee, Italy). Image processing and morphometric analysis of the mandibular foramina was conducted using MIMICS software (Materialise, Belgium). Statistical analyses were performed using the Statistical Package for the Social Sciences (SPSS), version 28.0 (IBM SPSS Statistics, Armonk, NY, USA). The results of this investigation showed that midline lingual foramen was the most common form. Pukhtoon ethnicity had larger lingual foramen dimensions overall, while males exhibited larger measurements in terms of size. The Pukhtoon ethnic group exhibited a greater distance from landmarks to lingual foramen. The most prevalent shape of mental foramen was round. In terms of size and distance to landmarks, Pukhtoon showed longer measurements from mental foramen. The most typical horizontal location was next to the second premolar, and the most frequently observed vertical position was apical to the tooth's root apex. The round shape was the common for accessory mental foramen while irregular and oval shapes were more prevalent on both sides of accessory mandibular foramen. Additionally, oval shapes were observed to be more prevalent on the right and left side of mandibular foramen. Similarly, the mandibular foramen and accessory mandibular foramen dimensions and distance to landmarks were observed to be greater in Pukhtoon ethnicity. A weak but positive correlation was detected between mandibular foramen with ramus width, height, and length of the mandibular body. This study provided valuable insight and clinical reference values regarding dimensions and distances to anatomical landmarks of all foramina of the mandible for the Mahajir and Pukhtoon ethnicity in Pakistan as well as according to different sexes and sides, which potentially be useful during pre-surgical evaluation of the mandible.